FAKTOR–FAKTOR YANG MEMPENGARUHI TERJADINYA KENAKALAN REMAJA - Riamah, Elfa Zuriana (Menara Ilmu, 2018)
Juvenile delinquency is a behavior carried out by teenagers by ignoring the social valuesthat apply in society. Juvenile delinquency encompasses all behaviors that deviate from thenorms and laws of teenagers. This behavior can harm himself and the people around him.Based on data from the Metro Jaya Regional Police of Pekanbaru in 2015 the number ofjuvenile delinquency did increase from year to year, the purpose of this study was to findout "Factors Affecting the Occurrence of Juvenile Delinquency in the Special ChildDevelopment Institution (LPKA) Class IIB Pekanbaru".This type of research is quantitative with descriptive design. The study was conducted atthe Child Special Guidance Institute (LPKA) Class IIB Pekanbaru in 2018. The populationin the study were all teenagers in the Pekanbaru Special Child Development Institution(LPKA) Class IIB which amounted to 61 teenagers, with a sample taken 61 people bysampling method namely sampling and analysis techniques are univariate.The results obtained based on the factors that influence the occurrence of juveniledelinquency based on self-factors that affect 41 people (67%) that did not affect 20 people(33%), family environmental factors that affect 48 people (78%) which did not affect 13people (21%), community environmental factors affecting 36 people (59%) that did notaffect 25 people (41%), school environment factors that affected 31 people (51%) whichdid not affect 30 people (49%)The conclusions in this study are that the factors that influence the occurrence of juveniledelinquency in the Child Special Development Institution (LPKA) Class IIB Pekanbaru in2018, factors that come from themselves, family environmental factors, communityenvironment, and school environmental factors.Keywords: Juvenile Delinquency Factors, TeenagersBibliography: 13 (2008-2017)